Optimalisasi Laba Warung Depot Ijo Kamal Melalui Analisis CVP dan Strategi Pendanaan - Yunita Putriani; Ameyla Nadhira Tsurayya; Hoitul Anam; Septiana Devita Nurfadela; Mardiana Mardiana; Mochamad Reza Adiyanto (Universitas 45 Surabaya, 2025)
This study aims to analyze the application of Cost-Volume-Profit (CVP) analysis and funding strategies for profit optimization at Warung Depot Ijo Kamal, a small business in the food industry. The research explores how financial management, including cost control and strategic funding, contributes to the business’s sustainability and growth. A descriptive qualitative approach was used, involving semi-structured interviews with the business owner and direct observations of daily operations. Data from financial reports were also collected for analysis. The findings revealed that Warung Depot Ijo Kamal achieves profitability above the break-even point, with a monthly profit of IDR 9,170,000. The analysis of funding sources indicated that the business relies on personal capital and cooperative loans, but further diversification of funding sources is recommended to support future expansion. The study also identified challenges in cash flow management, particularly in meeting employee salary obligations. Recommendations include improving cash flow planning, diversifying funding sources, and exploring external financing options to support business growth. This research provides valuable insights for small business owners seeking to optimize profits and ensure long-term sustainability.